Afghanistan EFL Lecturers and Students' Attitudes towards Paktia-University Languages and Literature Faculty English Department Curriculum by Using CIPP Model - Wahidullah Alokozay; Noor Agha Noori; Sultan Zahid (RIRAI Publisher, 2023)
The goal of this study is to evaluate the English department curriculum at Afghanistan Paktia University from the perspectives of EFL lecturers and students in accordance with the CIPP Model which has four dimensions; Context, input, process, and product. The research used a quantitative approach to collect data from 88 lectures and students which analyzed using SPSS version 24. The replies of the participants were ascertained using descriptive statistics (frequency, mean, and standard deviation) and inferential statistics (t-test). The outcome proved that the English-Department curriculum at Paktia University's Languages and Literature Faculty received favorable evaluations from both the lecturer and the students. Study restrictions made it clear that a mixed-method study may be conducted to produce more credible results.